The People’s Participation in Setting up The Development Plan of Wanghinlad Tambon Administration Organization ,Chumphae District,Khon Kaen Province. - พลังภูเขียว สุเมธ (Journal of Graduate MCU KhonKaen Campus, 2014)
This research aims to: 1) Study people’s participation in setting up the development plan of Tambon Admonistration Organization, Chomphae district in Khon Kaen province, and 2) to compare people’s participation in the development plan of Tambon Administration Organization classified by gender, age, level of education, occupation, and monthly income. The sample group was 376 people who were eighteen years old and older who live in Wang Hinlad sub-district, Chumpae district in Khon Kaen province. Research instruments included a set of questionnaire. The data was analyzed for frequency and percentage. The findings showed that among 376 samples, 50.53% of them were females with 40.96% of 50 years old of age and older. It was found that 59.57% were elementary school graduates, 57.98% were farmers and 52.93% earned 5,000-10,000 baht income per month. The overall situation of participation in the development plan of Wang Hinlad Tambon Administration Organization was at low level. When considering in each aspect, it was showed that participation in planning and decision making , and proceed as planned were at high level. The aspect of evaluation and following up were at low level. When comparing levels of participation it was found that the people with different genders, ages, occupations, educational levels, and income levels had no differences in their levels of participation.